(Na0.5Bi0.5)0.7Sr0.3TiO3 modified by Bi(Mg2/3Nb1/3)O3 ceramics with high energy-storage properties and an ultrafast discharge rate. Issue 7 (20th December 2019) - Lin, Ying; Li, Da; Zhang, Miao; Yang, Haibo
Abstract : Novel (Na0.5 Bi0.5 )0.7 Sr0.3 TiO3 -based lead-free ceramics with vastly improved energy-storage properties for high power system applications. Abstract : The design of ceramic dielectrics with high energy-storage properties and outstanding temperature stability is an important but challenging topic in advanced electronic and electrical power systems. Here, we utilized a strategy to achieve synergistic enhancement of energy density and energy efficiency in the (1 − x )(Na0.5 Bi0.5 )0.7 Sr0.3 TiO3 – x Bi(Mg2/3 Nb1/3 )O3 systems based on refined grain size and the introduction of Bi 3+ 's lone pair electron 6s 2 configuration, respectively. As a result, a giant discharge energy density of 3.45 J cm −3 and a high energy efficiency of 88.01% were simultaneously achieved in the 0.85NBST–0.15BMN ceramic, which precede those of recently reported lead-free dielectric ceramic materials. Meanwhile, excellent temperature (30–150 °C) and frequency (1–100 Hz) stability were also observed at 200 kV cm −1 . Moreover, an outstanding power density ( P D ) of 38.47 MW cm −3 and an ultrafast discharge rate ( t 0.9 ) of 52.8 ns were also achieved in the 0.85NBST–0.15BMN ceramic at 120 kV cm −1 . These results may provide a feasible approach to develop more NBST-based lead-free ceramics with vastly improved energy-storage properties.